The Effectiveness of Acceptance and Commitment Therapy on Achievement Motivation and Quality of Life among Female High School Students in Sari - Eftekhar-Sadat Samadi; Ramezan Hasanzadeh; Yarali Dousti (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Acceptance and commitment therapy is among the ways to increase student's achievement motivation and quality of life. Therefore, the aim of the present study is to determine the effectiveness of acceptance and commitment therapy on the achievement motivation and quality of life among female high school students in Sari in northern Iran. Materials and Methods: The design of this study was semi-experimental with a pre-test, followed by a test with a control group. Participants included female high school students in Sari who were randomly assigned to two experimental and control groups. Data were collected via the Achievement Motivation and Quality of Life Scale at school. The analysis of covariance was used for data analysis by using SPSS-21 software. Results: Responses of 30 female high school in the experimental group and 30 in the control group were analyzed. The mean (SD) age of the experimental group was 16.1 (2.4) and 16.6 (3.1) respectively. Acceptance and commitment therapy increased the achievement motivation among the experimental group from 50.6 (7.6) to 73.6 (6.8), P<0.001. In addition, the quality of life of participants among the experimental group was improved from 62.2 (7.6) to 89.1(7.6), P<0.001. On the other hand, the achievement motivation and quality of life of the control group did not show a significant difference in pre-test and post-test. Conclusion: Acceptance and commitment therapy increased achievement motivation and quality of life at school among high school student.